Screening for GJB2 and GJB6 gene mutations in patients from Campania region with sensorineural hearing loss. - Chinetti, Viviana; Iossa, Sandra; Auletta, Gennaro; Laria, Carla; De Luca, Maria; Di Leva, Francesca; Riccardi, Pasquale; Giannini, Pasquale; Gasparini, Paolo; Ciccodicola, Alfredo; Marciano, Elio; Franzè, Annamaria (Int J Audiol, 2010)
The aim of this study was to screen 349 patients affected by sensorineural hearing loss (SNHL), mostly from the Campania region (southern Italy), for GJB2 gene mutations and for two deletions of the GJB6 gene (del GJB6 -D13S1830 and del GJB6 -D13S1854). We identified pathogenetic GJB2 mutations in 51 cases (15% of patients). No GJB6 mutation was found. We also examined the audiologic features of the patients for whom we had an etiologic diagnosis, in order to identify correlations between the severity of hearing loss and the type of mutation.
Keywords: Acoustic Stimulation; Adolescent; Adult; Audiometry; Auditory Perception; Child; Child, Preschool; Connexins; Genetic Predisposition to Disease; Genetic Testing; Hearing Loss, Sensorineural; Heterozygote; Homozygote; Humans; Italy; Mass Screening; Middle Aged; Mutation; Phenotype; Risk Factors; Severity of Illness Index; Young Adult